Prenatal Corticosteroids Modify Glutamatergic and GABAergic Synapse Genomic Fabric: Insights from a Novel Animal Model of Infantile Spasms. (28th October 2013) - Iacobas, D. A.; Iacobas, S.; Chachua, T.; Goletiani, C.; Sidyelyeva, G.; Velíšková, J.; Velíšek, L.
Abstract : Prenatal exposure to corticosteroids has long‐term postnatal somatic and neurodevelopmental consequences. Animal studies indicate that corticosteroid exposure‐associated alterations in the nervous system include hypothalamic function. Infants with infantile spasms, a devastating epileptic syndrome of infancy with characteristic spastic seizures, chaotic irregular waves on interictal electroencephalogram (hypsarhythmia) and mental deterioration, have decreased concentrations of adrenocorticotrophic hormone (ACTH) and cortisol in cerebrospinal fluid, strongly suggesting hypothalamic dysfunction. We have exploited this feature to develop a model of human infantile spasms by using repeated prenatal exposure to betamethasone and a postnatal trigger of developmentally relevant spasms with NMDA. The spasms triggered in prenatally primed rats are more severe compared to prenatally saline‐injected ones and respond to ACTH, a treatment of choice for infantile spasms in humans. Using autoradiography and immunohistochemistry, we have identified a link between the spasms in our model and the hypothalamus, especially the arcuate nucleus. Transcriptomic analysis of the arcuate nucleus after prenatal priming with betamethasone but before trigger of spasms indicates that prenatal betamethasone exposure down‐regulates genes encoding several important proteins participating in glutamatergic and GABAergic transmission. Interestingly, there were significant sex‐specific alterations after prenatal betamethasone in synapse‐related gene expression but no such sex differences were found in prenatally saline‐injected controls. A pairwise relevance analysis revealed that, although the synapse gene expression in controls was independent of sex, these genes form topologically distinct gene fabrics in males and females and these fabrics are altered by betamethasone in a sex‐specific manner. These findings may explain the sex differences with respect to both normal behaviour and the occurrence and severity of infantile spasms. Changes in transcript expression and their coordination may contribute to a molecular substrate of permanent neurodevelopmental changes (including infantile spasms) found after prenatal exposure to corticosteroids.